2006
DOI: 10.1063/1.2387950
|View full text |Cite
|
Sign up to set email alerts
|

Using neural networks to represent potential surfaces as sums of products

Abstract: By using exponential activation functions with a neural network (NN) method we show that it is possible to fit potentials to a sum-of-products form. The sum-of-products form is desirable because it reduces the cost of doing the quadratures required for quantum dynamics calculations. It also greatly facilitates the use of the multiconfiguration time dependent Hartree method. Unlike potfit product representation algorithm, the new NN approach does not require using a grid of points. It also produces sum-of-produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
148
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(150 citation statements)
references
References 50 publications
0
148
0
2
Order By: Relevance
“…Fitting potential energy surfaces (PESs) and electrostatic multipole moment surfaces of small molecules to data generated by first principles electronic structure calculations has been a mainstay of computational chemistry for decades 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Typically, when modelling the PES of a small group of atoms, the list of pairwise distances is used or, equivalently, some transformed version of the interatomic distances, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fitting potential energy surfaces (PESs) and electrostatic multipole moment surfaces of small molecules to data generated by first principles electronic structure calculations has been a mainstay of computational chemistry for decades 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Typically, when modelling the PES of a small group of atoms, the list of pairwise distances is used or, equivalently, some transformed version of the interatomic distances, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…of terms represented PES by the choice of the neuron. Specifically, using a simple exponential function, g x ð Þ5e x together with g out x ð Þ5x, a SOP form is easily obtained (which we call expnn [108] ):…”
Section: Transformed Coordinates and Dimensionality Reductionmentioning
confidence: 99%
“…The error of the expnn PES is comparable to the cumulative error of the original 1 potfit fits. [25,26,108] Brown and coworkers have used expnn to fit a PES of CS 2 to highly accurate ab initio data and to compute its vibrational levels. [117] They also showed that expnn can be interfaced with the multiconfiguration time dependent Hartree algorithm.…”
Section: Transformed Coordinates and Dimensionality Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PES can be forced into SOPs form by using, for example, potfit [5,97], multigrid potfit [98], or neural network methods [99][100][101].…”
Section: Using Rank Reduction To Avoid Storing Full Dimensional Vectorsmentioning
confidence: 99%